2011
DOI: 10.1186/1478-7547-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Health economic evaluations comparing insulin glargine with NPH insulin in patients with type 1 diabetes: a systematic review

Abstract: BackgroundCompared to conventional human basal insulin (neutral protamine Hagedorn; NPH) the long-acting analogue insulin glargine (GLA) is associated with a number of advantages regarding metabolic control, hypoglycaemic events and convenience. However, the unit costs of GLA exceed those of NPH. This study aims to systematically review the economic evidence comparing GLA with NPH in basal-bolus treatment (intensified conventional therapy; ICT) of type 1 diabetes in order to facilitate informed decision making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the pharmacokinetic profile of long‐acting insulin analogues is believed to provide the potential of reduced daily injection frequencies. This propensity may also have implications for health economical calculations . Whether these theoretical advantages are reflected in the ‘real‐life’ setting of patient care outside of randomized controlled studies is currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pharmacokinetic profile of long‐acting insulin analogues is believed to provide the potential of reduced daily injection frequencies. This propensity may also have implications for health economical calculations . Whether these theoretical advantages are reflected in the ‘real‐life’ setting of patient care outside of randomized controlled studies is currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that insulin glargine is superior to neutral protamine Hagedorn (NPH) insulin in reducing the fasting blood glucose value, the hemoglobin A1c (HbA1c) value, and the number of nocturnal hypoglycemias in T1DM patients. [10][11][12][13][14][15] Glargine appeared to be cost-effective or even cost saving among T1DM patients with basal bolus therapy from the perspective of statutory health insurance compared with NPH depending on the scenario chosen. 16 The aim of this study was to compare insulin glargine and NPH insulin, in terms of resource consumption and directly associated treatment costs, in T1DM patients receiving ICT.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of dealing with overall cost issues was shown in an analysis that found only 6 studies (out of 382 publications between 2000 and 2009) offered data on both the acquisition costs of glargine versus NPH in patients with type 1 diabetes but also on clinical effects, diabetes complications, quality of life, fear of hypoglycemia, etc. (22). In one study, glargine was less expensive and in four additional studies use of glargine was deemed "good value" (i.e., cost $4,420-$17,946; 3,227-13,100 euro per quality-adjusted life-years gained) (23).…”
mentioning
confidence: 99%